The economic collapse and school practice in Reykjavik - Lárusdóttir, Steinunn Helga; Sigurðardóttir, Anna Kristín; Jónsdóttir, Arna H.; Hansen, Börkur; Guðbjörnsdóttir, Guðný (Menntavísindasvið Háskóla Íslands, 2016)
Iceland. Earlier, a similar study was conducted by the same research team in two Icelandic municipalities, one in an agricultural area, and one in a fishing and service community. Information about staff and school costs was gathered for the years of 2013 and 2014. Interviews with individuals and in focus groups were carried out with represenatives at the ministry of culture and education, the Local Education Authorities in Reykjavík, school administrators, teachers, other staff, parents and pupils of six selected schools: two preschools, two primary and lowersecondary schools and two upper-secondary schools. Information about staff and school costs was also gathered. The research was qualitative in nature, primarily based on interviews and documentary data. Interviews were conducted with individuals and in focus groups with representatives of the municipalities and the state, school administrators, teachers, parents and pupils of selected pre-, primary-, and upper-secondary schools. The research sought answers to the following questions: How did educational authorities and school professionals respond to budget cut requirements? Did the reductions cause a school crisis and did they have different consequences depending on the school level? The findings suggest that the core functions of the schools, teaching and learning, were to a large extent protected as stipulated by school authorities. Reduction in expenditure, therefore, did not cause a school crisis in the sense, that the basic values of the schools were threatened. This, however, may not apply to the preschools and the schools at the upper secondary level, which were harder hit by the cut-backs than the other school levels. Even if the schools were able to protect the core school activities, finanicial cutbacks had serious implications for the schools. Various cutbacks were made at all school levels; administrative positions, especially at the middle levels, were cut considerably, principals served as substitute teachers, classes became bigger, no ...